Regional integration and multilateral cooperation in the global economy - Teunissen, Jan Joost ed. (FONDAD The HagueNL, 1998)
Focuses on the question - how can regional integration contribute optimally to national development as well as to multilateral cooperation. Looks at Europe, Asia and Latin America, and Africa and the Middle East in this regard. Examines the new regionalism and looks at security and development. Highlights the policy challenges of globalisation and regionalisation.